Sistem Monitoring dan Smart Farming untuk Peternakan Anak Ayam Berbasis Internet of Things (IoT) - Eka Prasetya, Erlangga; Fadillah, Nurul; Satriyo, Satriyo; Rusman, Rusman; Yuwono Tharam , Medi (Electrical Network Systems and Sources, 2023)
This final project discusses the implementation of an Internet of Things (IoT)-based Monitoring System and Smart Farming for chicken farming. This technological innovation aims to enhance productivity and sustainability in the livestock industry. By connecting sensors to the IoT network, farmers can monitor the real-time conditions of the poultry house, such as temperature, humidity, and air quality. The objective of this writing is to design an IoT-based monitoring and smart farming system specifically for use in chicken farming. This system will enable real-time area monitoring, automation of feeding and drinking processes, and data management for farmers. The benefits of this proposal for students include enhancing knowledge about IoT and monitoring systems in the field of poultry farming. In related fields of study, this final project will provide an understanding of IoT application in agriculture and livestock. Meanwhile, for farmers and the livestock industry, the benefits lie in improving the productivity and quality of poultry farming.